2018
DOI: 10.3766/jaaa.17016
|View full text |Cite
|
Sign up to set email alerts
|

Upgrade to Nucleus® 6 in Previous Generation Cochlear™ Sound Processor Recipients

Abstract: The Nucleus® 6 sound processor is now compatible with the Nucleus® 22 (CI22M)—Cochlear’s first generation cochlear implant. The Nucleus 6 offers three new signal processing algorithms that purportedly facilitate improved hearing in background noise.These studies were designed to evaluate listening performance and user satisfaction with the Nucleus 6 sound processor.The research design was a prospective, single-participant, repeated measures designA group of 80 participants implanted with various Nucleus intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
5
0
5
Order By: Relevance
“…The majority of studies to date have evaluated the benefit of a specific processor from one implant company. For example, clinical studies have confirmed the advantage of the upgrade to the CP810 [ 18 ], the C910 [ 4 , 20 , 22 , 25 ], the CP1000 [ 27 ], the Rondo [ 17 ], and the Opus 2 [ 14 , 24 ]. By contrast, individual studies explicitly evaluate individual technological innovations of a new speech processor in the context of reprovisioning, for example, the effect of specific directional microphone modes [ 19 ], signal processing strategies [ 21 ], or the speech processor’s connectivity to external devices [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies to date have evaluated the benefit of a specific processor from one implant company. For example, clinical studies have confirmed the advantage of the upgrade to the CP810 [ 18 ], the C910 [ 4 , 20 , 22 , 25 ], the CP1000 [ 27 ], the Rondo [ 17 ], and the Opus 2 [ 14 , 24 ]. By contrast, individual studies explicitly evaluate individual technological innovations of a new speech processor in the context of reprovisioning, for example, the effect of specific directional microphone modes [ 19 ], signal processing strategies [ 21 ], or the speech processor’s connectivity to external devices [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the divergent measurement methodology in the individual studies with regard to the speech material used and the test sound pressure levels used, a cross-study evaluation of the benefit of speech processor conversion is hardly possible. Based on the current state of studies, an average improvement of 3–15% is found for monosyllabic test words at 60–65 dB SPL [ 4 , 14 , 18 , 23 , 24 ]. When measuring with multisyllabic numbers, previous studies have not found a significant improvement related to the upgrade, which at this point can be attributed to a ceiling effect [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both loaned processors, the T and C levels of the participants' favorite everyday program were used and adjusted if required. The signal processing algorithms automatic sensitivity control (41), adaptive dynamic range optimization (41), SNR-based noise reduction (42), and wind noise reduction (42) were enabled, and the automatic scene classification (SCAN, 42) was disabled in all programs. One program using the adaptive directional microphone Beam was uploaded to the OTE1 (condition OTE1-Beam).…”
Section: Methodsmentioning
confidence: 99%